Campur Kode dalam Diskusi Mahasiswa Semester IV Program Studi Pendidikan Bahasa Indonesia FKIP Universitas PGRI Palembang - Contessa, Emilia; Sucipto, Ridho Andi (Multiverse: Open Multidisciplinary Journal, 2023)
This research examines code mixing in student discussions during the fourth semester of the Language Education Study Program at PGRI University, Palembang. Code mixing involves the use of a main code alongside other codes that lack function or autonomy. Descriptive methodology is employed, using fourth-semester students as participants. Data analysis employs the intralingual equivalent technique, while data collection involves observation and recording. Results indicate that the highest percentage of code mixing (6.1%) occurs in the first recording, with 64 instances out of 1056 words. The lowest code mixing percentage (3.2%) is found in the fifth recording, with 15 instances out of 463 words. Overall, code mixing percentages for subsequent meetings range from 4.2% to 5.9%. This study sheds light on code mixing patterns in student discussions, contributing to language education research.